The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1186/s12902-020-00563-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of total bilirubin and indirect bilirubin content with metabolic syndrome among Kazakhs in Xinjiang

Abstract: Background: Some studies have shown that a high level of bilirubin is a protective factor against metabolic syndrome (MS), while a high level of transaminase is a risk factor for MS. However, the existing results are inconsistent and few cohort studies have been published. Methods: Using an ambispective cohort study, 565 Kazakhs from Xinjiang, China were selected as the study subjects. The baseline serum bilirubin and transaminase levels of the subjects were divided into quartiles and the relationship between … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
2
11
0
Order By: Relevance
“…Serum bilirubin levels, even within the normal range, might have graded associations with the prevalence of MS in children [37]. Similar results have also been reported in other studies conducted in Chinese [28,70], Korean [27,71], and Polish [57] adults.…”
Section: Discussionsupporting
confidence: 88%
“…Serum bilirubin levels, even within the normal range, might have graded associations with the prevalence of MS in children [37]. Similar results have also been reported in other studies conducted in Chinese [28,70], Korean [27,71], and Polish [57] adults.…”
Section: Discussionsupporting
confidence: 88%
“…Data from National Health and Nutrition Examination Survey (NHANES) suggested that bilirubin levels were related to 26% lower risk of MetS [ 48 , 49 ]. Congruent with our results, inverse relationship between serum bilirubin levels and MetS components were also shown in cross-sectional studies involving 12,342 Korean adults [ 15 ], 1568 Polish adults [ 50 ], and cohort study of 565 Kazakhs [ 51 ]. Moreover, bilirubin has been speculated to be a potential pre-disease biomarker for the development of MetS in asymptomatic Slovenian individuals [ 13 ], however, in comparison to our study, those studies had smaller sample size.…”
Section: Discussionsupporting
confidence: 89%
“…The serum total bilirubin concentrations in the present study were inversely associated with the insulin resistance risk. Previous studies also reported that serum total bilirubin concentrations are inversely related to the MetS risk in various ethnic groups [ 43 , 44 , 45 , 46 ]. It might be associated with the cholesterol metabolism in the liver.…”
Section: Discussionmentioning
confidence: 86%